2015
DOI: 10.3168/jds.2014-8154
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and lying behavior of heat-stressed early lactation cows fed low fiber diets containing roughage and nonforage fiber sources

Abstract: In addition to reduced nutrient intake, an environmental thermal load may directly affect milk yield in heat-stressed dairy cows. Feeding and lying behaviors of early lactation cows fed low fiber diets containing neutral detergent fiber (NDF) from roughage and nonforage fiber sources (NFFS) were investigated under summer conditions in Thailand. Immediately after calving, 30 multiparous cows (87.5% Holstein × 12.5% Sahiwal) were randomly allocated to dietary treatments for 63 d in a completely randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Along with the increase in THI by 1 unit between the W and H periods, there was observed a decrease in LTD by 38 min/d in the cubicles, while in the manure alleys it increased by 15 min/d. The declines in lying bouts' length demonstrated by Allen et al (2015) and Kanjanapruthipong et al (2015) caused by an increase in THI were confirmed by LTH calculated in different areas of the barn. However, it is characteristic that despite very unfavourable conditions in the barn during the period between 12:00 pm and 04:00 pm, the cows staying in the feeding alley returned and lay down in the cubicles.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Along with the increase in THI by 1 unit between the W and H periods, there was observed a decrease in LTD by 38 min/d in the cubicles, while in the manure alleys it increased by 15 min/d. The declines in lying bouts' length demonstrated by Allen et al (2015) and Kanjanapruthipong et al (2015) caused by an increase in THI were confirmed by LTH calculated in different areas of the barn. However, it is characteristic that despite very unfavourable conditions in the barn during the period between 12:00 pm and 04:00 pm, the cows staying in the feeding alley returned and lay down in the cubicles.…”
Section: Discussionsupporting
confidence: 54%
“…According to Metz (1985) depriving cows of the possibility to have a rest in a lying position for 3 h, and according to Kanjanapruthipong et al (2015) for 2 h, causes a deterioration in an animal's welfare by disturbing their daily routine. In the H periods, after morning milking occurred depriving the possibility of lying for around 1 h, which resulted in a disturbance of cows comfort.…”
Section: Discussionmentioning
confidence: 99%
“…According to Legrand et al (2011), cows spend more time standing without feeding and less time lying as heat load increased. Based on the Kanjanapruthipong et al (2015) results, as THI was increased, the duration of feeding and lying time was decreased as well.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ambient heat load elicits variable behavioural responses, including reduced feed intake (Collier, Beede, Thatcher, Israel, & Wilcox, ), decreased meal length and therefore a lower rate of intake in dairy cows (Kanjanapruthipong, Junlapho, & Karnjanasirm, ). Under a high heat load, cows tend to eat more frequently and spend less time lying compared with cows that are not experiencing heat stress (Shiao et al, ).…”
Section: Introductionmentioning
confidence: 99%